Research on the Development and Visual Image of Opera Culture Creative Products - Xiaobing Hu; Yalin Zhang (ITB Journal Publisher, LPPM ITB, 2020)
Huangmeixi opera is an integral part of Chinese opera culture and its visual elements are a fountainhead for designers. This study focused on the development of Huangmeixi opera cultural creative products through refining the elements of Huangmeixi opera in points, lines, and colors, redesigning them from the aspects of element extraction, form abstraction, cultural implication abstraction, and exploring the cultural elements of Huangmeixi opera and product development strategy. The goal is to develop cultural creative products based on Huangmeixi opera.